The russian mentality - Styczyński, Marek (Hybris, 2014)
The present essay is the conclusion of my two books devoted to Nicolas Berdjaev’s religious philosophy: Amor futuri albo eschatologia zrealizowana Studia nad myślą Mikołaja Bierdiajewa (Amor Futuri or Eschatology Realised Studies on the Thought of Nicolas Berdjaev), [Styczyński 1992] and Umiłowanie przyszłości albo filozofia spraw ostatecznych. Studia nad filozofią Mikołaja Bierdiajewa (Adulation for the Future or the Philosophy of the Ultimate Matters Studies on the Thought of Nicolas Berdjaev), [Styczyński 2001]. The differences between them are mentioned in the latter. They were both written in Polish and as a consequence had no chance of reaching a wider circle of readers. This is, therefore, the reason why I have decided to present this conclusion to an English language readership. I have tried to show the consequences of the unique Russian mentality, whose predominant feature is an ambivalence between a persistent search for good and constantly doing of evil. This “Russian theodicy” expressing itself in the creation of an alternative world, which is to justify the evil done, has its roots in the conviction of man’s principally divine nature revealing itself through the exculpating effect of evil. In the case of the twentieth century of Russian history it yielded a result totally different from the expected one.